The Role of Natural Resources, Electricity Production, Economic Globalization, and R&D in CO2 Neutrality: An Empirical Investigation for Kuwait - Kisswani, Khalid M.; Al-Khasawneh , Jamal A.; Alam, Md Shabbir (International Journal of Energy Economics and Policy, 2025)
At the 27th conference of parties in Egypt, Kuwait declared the environmental agenda of turning carbon neutrality by 2050, and many nations have started progressing towards carbon neutral agendas. Environmental research and development are essential factors in achieving these goals. This paper examines the relationship between natural resources, R&D, electricity production, economic globalization, and CO2 emissions in Kuwait from 1975 to 2020. We employed unit-root tests to verify the integrative properties of the variables. Additionally, the FARDL method was used to analyze the relationship between the variables. The Fourier Toda-Yamamoto causality test is applied to explore the causal links between natural resources, economic globalization, electricity production, R&D, and CO2 emissions. The empirical findings reveal that these variables are cointegrated and imply long-run relationships. Moreover, R&D expenditures reduce CO2 emissions, while natural resources, electricity production, and economic globalization increase CO2 emissions. Based on the empirical results, this study suggests attaining the targets of SDG-07(clean and affordable energy), SDG-09 (R&D, innovations), and SDG-13 (climate change).